2021
DOI: 10.3390/foods10071514
|View full text |Cite
|
Sign up to set email alerts
|

Response of Lactiplantibacillus plantarum NMGL2 to Combinational Cold and Acid Stresses during Storage of Fermented Milk as Analyzed by Data-Independent Acquisition Proteomics

Abstract: To understand the mechanism of tolerance of lactic acid bacteria (LAB) during cold storage of fermented milk, 31 LAB strains were isolated from traditional fermented products, and Lactiplantibacillus plantarum NMGL2 was identified with good tolerance to both cold and acid stresses. Data-independent acquisition proteomics method was employed to analyze the response of Lpb. plantarum NMGL2 to the combinational cold and acid stresses during storage of the fermented milk made with the strain at 4 °C for 21 days. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 39 publications
0
7
0
Order By: Relevance
“…They are Gram-positive, catalase-negative, non-spore-bearing, non-motile, facultative anaerobic microorganisms and are considered as important probiotics for human health [ 9 ]. Any LABs suitable for industrial production should have good fermentation performance and strong tolerance, so that these microorganisms can survive during the process of production, in storage, and also in the gastrointestinal tract after being consumed by humans [ 10 , 11 ]. Among the unfavorable environmental challenge factors, alcohol, as a bacteriostatic organic reagent, can cause harmful changes in the cell membrane permeability of bacteria [ 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…They are Gram-positive, catalase-negative, non-spore-bearing, non-motile, facultative anaerobic microorganisms and are considered as important probiotics for human health [ 9 ]. Any LABs suitable for industrial production should have good fermentation performance and strong tolerance, so that these microorganisms can survive during the process of production, in storage, and also in the gastrointestinal tract after being consumed by humans [ 10 , 11 ]. Among the unfavorable environmental challenge factors, alcohol, as a bacteriostatic organic reagent, can cause harmful changes in the cell membrane permeability of bacteria [ 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…This gene in Mycobacterium fortuitum is involved in acid stress response [ 71 ]. Gene rbfA encoding ribosome-binding factor was up-regulated by 2.53 times, and this gene in Lactobacillus plantarum NMGL2 (recently reassigned as Lactiplantibacillus plantarum NMGL2) has been reported to be involved in the response to acid stress and cold stress [ 72 ]. Gene mazF was up-regulated by 2.25 times in liquid-state fermented cells, and this gene has been found to be activated under acid stress in Bifidobacterium longum [ 73 ].…”
Section: Resultsmentioning
confidence: 99%
“…Primarily, these strains were identified based on Gram reaction, catalase tests and cell morphology. Strains level identification was performed using API 50 CHL test (bio-Merieux, Marcy-l’Étoile, France) and 16S rDNA sequencing analysis as previously described by (Aziz, T., et al, 2022; 2021; 2020a; 2020b and 2020c; Jian et al; 2017 and 2020; Zhang et al, 2022 and 2020; Yunyun et al 2018; Wang et al, 2015) [ 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 ].…”
Section: Methodsmentioning
confidence: 99%
“…In our previous studies, L. plantarum YW11 strain isolated from Tibetan Kefir grains has demonstrated modulatory effects on gut dysbacteriosis [ 36 ], improving immune response and ameliorating inflammatory bowel disease (IBD) [ 37 ], as well as tolerance to acid and bile stress [ 38 ]. Similarly, we have also reported that Lp YW11 can be used as functional agent in the processing of fermented dairy products with enhanced textural stability and cholesterol-lowering, antioxidant, and antibiofilm bioactivities [ 39 ], and it has the capability of biotransformation of linoleic acid (LA) to conjugated linoleic acid (CLA) [ 33 ]. In addition to that we also reported that this strain L. plantarum 13-3 and 12-3 are also capable of converting LA to certain fatty acid metabolites [ 34 , 35 ].…”
Section: Introductionmentioning
confidence: 99%